PATIENTS WITH EPILEPSY WITH THE WRONG CHOICE OF ANTIEPILEPTIC DRUG AND WITH ENDOCRINOLOGICAL DISORDERS (Modern education and development, 2025)
The psychological impact of epilepsy can seriously affect a person's well-being and quality of life. The unpredictability of seizures and the fear of seizures in public or at inconvenient times can cause significant emotional distress. People with epilepsy may experience anxiety, fear, and worry about when the next seizure will occur, which affects their overall mental health and well-being. Depression is common in people with epilepsy. Epilepsy is a neurological disorder characterized by recurrent seizures caused by abnormal electrical activity in the brain. Although epilepsy affects people in different ways, there are several toxicities associated with the condition that can affect people's quality of life. In three articles, we will look at some of the harmful factors of epilepsy and the problems that people living with this disease face.